Orally Administered Plasmalogens Alleviate Negative Mood States and Enhance Mental Concentration: A Randomized, Double-Blind, Placebo-Controlled Trial - Fujino, Minoru; Fukuda, Jun; Isogai, Hirohisa; Ogaki, Tetsuro; Mawatari, Shiro; Takaki, Atsushi; Wakana, Chikako; Fujino, Takehiko (Frontiers in Cell and Developmental Biology, 2022)
Background: Plasmalogens have been shown to improve neurodegenerative pathology and cognitive function. We hypothesized that plasmalogens work in small amounts as a kind of hormone interacting with a G protein-coupled receptor, and then explored the effects of scallop-derived purified plasmalogens on psychobehavioral conditions in a randomized placebo-controlled trial of college athletes in Japan. Methods and materials: Eligible participants were male students aged 18 to 22 years who belonged to university athletic clubs. They were randomly allocated to either plasmalogen (2 mg per day) or placebo treatment of four weeks’ duration. The primary outcome was T-score of the Profile of Mood States (POMS) 2–Adult Short, and the secondary outcomes included the seven individual scales of the POMS 2, other psychobehavioral measures, physical performance, and laboratory measurements. The trial was registered at the Japan Registry of Clinical Trials (jRCTs071190028). Results: Forty participants (20 in plasmalogen group and 20 in placebo group) completed the four-week treatment. The Total Mood Disturbance (TMD) score of plasmalogen group showed a greater decrease at 4 weeks than that of placebo group while between-group difference was marginally significant (P = 0.07). The anger-hostility and fatigue-inertia scores of the POMS 2 decreased significantly in plasmalogen group, but not in placebo group, at 4 weeks. Between-group differences in those scores were highly significant (P = 0.003 for anger-hostility and P = 0.005 for fatigue-inertia). Plasmalogen group showed a slight decrease in the Athens Insomnia Scale at 2 weeks, and the between-group difference was near-significant (P = 0.07). The elapsed time in minute-patterns on the Uchida-Kraepelin test, which is a marker of mental concentration, revealed significantly increased performance in plasmalogen group compared with placebo group. There were no between-group differences in physical and laboratory measurements. Conclusion: It is suggested that orally administered plasmalogens alleviate negative mood states and sleep problems, and also enhance mental concentration.